Intrusion of Polyethylene Glycol during Osmotic Tests: Identifying Cellulose Acetate Degrading Microbes - Mohd Yuhyi, Mohd Tadza; Mohd Fazli, Farida Asras; Muhammad Afiq, Mohd Tadza; Jamil, Ismail; Nurhidayah, Mahazam; Nurul Shafiqah, Mohd Azmi (Penerbit Universiti Teknologi Malaysia, 2016)
Cellulose acetate semipermeable membranes and polyethylene glycol (PEG) solutions are commonly used to apply suction in soils using the osmotic technique. The structural integrity of the membrane is crucial to maintain a consistent suction value throughout a test. The membrane however, is vulnerable to microbial attack, which in turn could lead to intrusion of PEG into soil specimens. In this study, osmotic test was carried out on initially saturated Andrassy bentonite specimen. PEG 6000 and membrane with molecular weight cut-off (MWCO) value of 3500 was used to apply suction of 3.4 MPa. Soil specimen and PEG solution after the osmotic test were examined for the presence of any potential cellulose or acetate degrading microbes. Test results indicated that both cellulose degrading bacteria and fungi were present in the PEG solutions. Addition of penicillin was found to be less effective in removing these microbes. However, 70% ethanol may be used to prevent cross contamination during handling of specimens. It is anticipated that eliminating these microbes is crucial to prevent intrusion of PEG in osmotic tests.